Insufficient Vitamin D Status at Birth Is Corrected by Vitamin D Supplementation (1000 IU/Day) With Increases in Lean Mass Evident at 12 Months of Age in Healthy Term Infants. (7th June 2021) - Razaghi, Maryam; Vanstone, Catherine A; Gharibeh, Nathalie; Sotunde, Olusola F; Wei, Shuqin; McNally, Dayre; Rauch, Frank; Jones, Glenville; Kimmins, Sarah; Weiler, Hope A
Abstract: Objectives: The primary objective was to test whether rapid correction of insufficient vitamin D status initiated in the neonatal period improves whole-body lean mass across infancy. Methods: This was a double-blinded, parallel-group, randomized controlled trial (NCT02563015). Healthy term breastfed infants of appropriate weight for gestational age (AGA) were recruited from Montreal (March 2016–2019). Capillary blood was collected (24–36 h) for serum 25-hydroxyvitamin D [25(OH)D] measurement (Liaison, Diasorin Inc.). Infants with serum 25(OH)D < 50 nmol/L were randomized to receive 400 (group 1, n = 49) or 1000 IU/d (group 2, n = 49) until 12 mo of age. Those with 25(OH)D ≥ 50 nmol/L were recruited to form a reference group, receiving 400 IU/d (group 3, n = 41). Anthropometry, body composition (dual-energy x-ray absorptiometry), and 25(OH)D concentrations were assessed at 1, 3, 6, and 12 mo. Differences between trial and reference groups were tested using mixed model repeated measures ANOVA adjusting for maternal pregnancy weight gain, infant sex, skin color, actual age at assessment, and breastfeeding status. Data are mean ± SD. Results: Infants (81 males, 58 females) were 39.6 ± 1.0 wk GA and 3388 ± 372 g at birth. By design, infants in group 1 and 2 had lower serum 25(OH)D concentrations at birth compared to group 3 (31.1 ± 9.3,  34.4 ± 12.0 vs. 68.0 ± 13.2 nmol/L,  respectively, P < 0.0001). On average, both trial groups achieved and maintained vitamin D sufficiency (25(OH)D ≥ 50 nmol/L) from 3 to 12 mo. Lean mass was not different among groups at baseline, but at 12 mo was higher in group 2 compared to group 1 (7012.5 ± 904.6 vs. 6690.4 ± 1121.7 g,  P = 0.0075; 4.8% difference), and not different from the reference group (7012.5 ± 904.6 vs. 6715.1 ± 784.6 g,  P = 0.2882). Weight, length, and whole-body fat mass were not different among groups at any time-point. Conclusions: Vitamin D supplementation (400 and 1000 IU/d) corrects insufficient stores, whereas the higher dosage of 1000 IU/d, modestly increases lean mass of otherwise healthy AGA term born infants by 12 mo of age without altering weight or length. These data concur with observations in weanling rats where increased vitamin D intakes elevated lean mass. The long-term benefits require further research. Funding Sources: Funded by Canadian Institutes of Health Research.